Post-traumatic stress symptoms in childhood brain tumour survivors and their parents - Bruce, M; Gumley, D; Isham, L; Fearon, P; Phipps, K (Wiley, 2010)
Objectives  This study aimed to investigate post-traumatic stress symptoms (PTSS) in childhood brain tumour survivors and their parents. A further aim was to explore the relationship between objective illness parameters, parent–child interactions, coping styles and PTSS.